A Frequency Compensation Algorithm of Four-Wheel Coherence Random Road. (18th September 2013) - Feng, Jun; Zhang, Xinjie; Guo, Konghui; Ma, Fangwu; Karimi, Hamid Reza
Abstract : The road surface roughness is the main source of kinematic excitation of a moving vehicle, which has an important influence on vehicle performance. In recent decades, random road models have been widely studied, and a four-wheel random road time domain model is usually generated based on the correlation of the four-wheel input, in which a coherence function is used to describe the coherence of the road input between the left and right wheels usually. However, during our research, there are some conditions that show that the road PSD (power spectral density) of one wheel is smaller than the other one on the same axle. Actually, it is caused by the uncorrelation between the left- and right-wheel road surface roughness. Hence, a frequency compensation algorithm is proposed to correct the deviation of the PSD of the road input between two wheels on the same axle, and it is installed in a 7-DOF vehicle dynamic study. The simulation result demonstrates the applicability of the proposed algorithm such that two-wheel road input deviation compensation has an important influence on vehicle performances, and it can be used for a control system installed in the vehicle to compensate road roughness for damper tuning in the future.